Respuesta :

Answer:

Choice C is the answer.

Step-by-step explanation:

We have given two functions.

f(x) = 2x² - 5x -3 and g(x) = 2x² + x

We have to find  (f/g) (x) .

The formula to find  (f/g) (x)  is :

(f/g) (x)  = f(x) / g(x)

Simplifying f(x) and g(x) , we have

f(x)  = 2x²-6x+x-3

f(x)  =  2x(x-3)+1(x-3)

f(x) =  (2x+1)(x-3)

g(x)  =  x(2x+1)

Putting above values in formula , we have

(f/g)(x)  = (2x+1)(x-3) / x(2x+1)

(f/g)(x)  = x-3 / x

Denominator must not be zero.

(f/g)(x)  = x-3 / x , x ≠0